2019
DOI: 10.1002/hed.25413
|View full text |Cite
|
Sign up to set email alerts
|

Protocol driven outcomes in renal parathyroid surgery

Abstract: Background Patients who require surgery for renal hyperparathyroidism represent a special population that is at high risk for postoperative complications. To optimize their treatment, we developed a multidisciplinary approach to the perioperative management of these patients undergoing parathyroidectomy. Methods The Augusta University endocrine surgery parathyroid database was interrogated to identify dialysis‐dependent patients undergoing parathyroidectomy from 2005 to 2015. Numerous clinical parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Certainly, risk factor identification can guide replacement therapy and streamline patient discharge. Studies have consistently shown that implementation of parathyroidectomy protocol can improve perioperative outcomes [26, 27]. Our current practice has reduced the hospital stay by 2 days compared to our previous report and maintained a low readmission rate.…”
Section: Discussionmentioning
confidence: 64%
“…Certainly, risk factor identification can guide replacement therapy and streamline patient discharge. Studies have consistently shown that implementation of parathyroidectomy protocol can improve perioperative outcomes [26, 27]. Our current practice has reduced the hospital stay by 2 days compared to our previous report and maintained a low readmission rate.…”
Section: Discussionmentioning
confidence: 64%
“…Renal patients are a special population with a completely different mechanism for their hyperparathyroidism, which requires a different pathophysiologic knowledge base, set of practice guidelines, 24 and surgical management protocols. 25 Nevertheless, the incidental surgical and anatomic education provided by exposure to these surgeries was enormously useful in refining intraoperative parathyroid identification strategies that apply directly and indirectly to patients with primary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients who had failed prior surgery, typical errors in radiographic interpretation and surgical conduct were better understood (eg, the most frequent location for a missed adenoma, the overly descended superior gland, was identified 23 ; this knowledge facilitated successful primary surgical interventions in our own practice). Renal patients are a special population with a completely different mechanism for their hyperparathyroidism, which requires a different pathophysiologic knowledge base, set of practice guidelines, 24 and surgical management protocols 25 . Nevertheless, the incidental surgical and anatomic education provided by exposure to these surgeries was enormously useful in refining intraoperative parathyroid identification strategies that apply directly and indirectly to patients with primary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%